Proposed new interior design of music centre for Yamaha Music Sdn Bhd at No 5 & 6 Sunway Giza, Dataran Sunway PJU 5 Kota Damansara, Petaling Jaya, Selangor Darul Ehsan / Abdul Mubin Rosman - Rosman, Abdul Mubin (Faculty of Architecture, Planning and Surveying, 2010)
The final study was to establish a new branch for the Yamaha Music Sdn.Bhd. The new branch will be created is in Kota Damansara, Selangor is the place to build in Malaysia because there are various facilities. Yamaha music is a company that sells tools and supplies of good music as well as the Yamaha also has its own music, which provides academic music courses. Before implementing this project, several studies have been carried out to meet client needs and goals. The study was performed including site selection studies, interview studies, observation studies, case studies and research with a questionnaire. Research and data collection process will be analyzed and applied in the design process to design a comfortable, attractive addition to creating a new image with a touch of style and image of its own.